Tuberculosis in anal fistula: incidence, clinical insights, and diagnostic challenges - Khan, Tariq Akhtar; Ali, Mohammad; Saha, Krishna Pada; Nashir Uddin, M.; Lutful Kabir Khan, M.; Muhsenin, Nunjirul; Nahar, Nazmun; Joarder, Sawantee; Kuddus Ali Khan, M. (International Surgery Journal, 2025)
Background: Tuberculosis (TB) is a rare but significant cause of anal fistula, often leading to diagnostic delays and suboptimal treatment. This study aimed to assess the incidence, clinical characteristics, and diagnostic challenges of TB in anal fistula cases. Methods: A prospective observational study was conducted from July 2023 to December 2024 at six hospitals in Bangladesh. A total of 85 patients with anal fistula underwent clinical evaluation, histopathological examination, and microbiological testing for TB. Fistulas were classified using the Parks and American gastroenterological association (AGA) systems. Demographic, clinical, and diagnostic data were analyzed using SPSS Version 25. Results: Among 85 patients, the mean age was 38.6 years, with a male predominance (80.0%). Inter sphincteric (48.2%) and low trans sphincteric (24.7%) fistulas were the most common types. Histopathology confirmed TB in 3.5% (3/85) of cases. All TB-positive cases presented with chronic non-healing fistulas, unhealthy granulation tissue, and were initially misdiagnosed. Simple fistulas accounted for 64.7% of cases, yet TB was identified in both simple and complex fistulas. Conclusions: TB should be considered in chronic or recurrent anal fistulas, especially in endemic regions. Routine histopathological examination is crucial for timely diagnosis. A combination of surgical intervention and anti-tubercular therapy (ATT) leads to favorable outcomes. Increased awareness among clinicians can help reduce diagnostic delays and improve patient management.